Imaging Modalities Role inRecurrent Acute Pancreatitis Diagnosis - Andreas Pekey; Rio Zakaria; Leonard Nainggolan; Ari Fahrial Syam; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Recurrent acute pancreatitis (RAP) is a potentially life-threatening pancreatic disorder. Itrequires a combination of medical and interventional skills to diagnose, determine the etiology, and treat the condition. Recurrencesoccur in 25-30% of all acute pancreatitis cases. The most common cause of RAP is gallstone (microlithiasis). Imaging modalities become an important aspect to evaluate multiple microlithiasis. In this case, we report a 52 years oldoverweight female with RAP and fatty liver ofunknown etiology.We suspected gallstone as the cause of RAP. Physical examination considered normal. Ultrasound and abdominal CT scan wasperformed in whichfatty liver were founded. Since the gallstone is not clearly found with radiologic imaging, we decide to undergoEndoscopic Retrograde Cholangiopancreatography(ERCP)procedure to evaluatea possibility of microlithiasis. ERCPresult showed a multiple microlithiasis, thus we evacuate the stones. Clinical outcome post ERCP and evacuationprocedure was good. We concluded that the best imaging modalities to evaluate microlithiasis in RAP with normal ultrasound and abdominal CT scan is ERCP.  Keywords:recurrent acute pancreatitis (RAP), microlithiasis, endoscopic retrograde cholangiopancreatography (ERCP).